Motivations of playing digital games: A review and research agenda. Issue 5 (28th December 2021) - Cheah, Isaac; Shimul, Anwar Sadat; Phau, Ian
Abstract: The global digital gaming industry has grown rapidly in recent years. Rapid technological advancements are changing the ways in which players can interact with video games as individuals and collectives. In addition to the increased penetration of games, the reasons for which people play and employ games need careful attention. In this paper, we have systematically reviewed the peer‐reviewed journal articles ( n  = 91) relevant to the gamers' motivations of playing digital games. In addition to analysing the publication trends, we have identified and discussed a set of six key motivational themes (immersion and flow, gratification and affect, escapism, social interaction, identification, and goal orientation). Subsequently, we call for further research on theoretical and methodological advancement as well as individual/social wellbeing and dark sides of digital gaming in relation to players' motivation.